The challenges of community development workers in the implementation of the Community Development Workers’ Programme in Makhado Local Municipality, Limpopo Province - Rikhotso, Rhandzavanhu Harris (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPA)--Stellenbosch University, 2013.